The post-marketing safety of venlafaxine: a real-world two-decade pharmacovigilance study using the FAERS database - Chokkakula, Santosh; Yang, Hualiang; Al-Masri, Abeer A.; Zhang, Yiquan; Naveen, Bommireddy; Yang, Bing (Frontiers in Pharmacology, 2026)
ObjectiveVenlafaxine, a serotonin-norepinephrine reuptake inhibitor widely prescribed for major depressive disorder and related conditions, remains insufficiently characterized regarding its adverse event profile. This study aimed to comprehensively evaluate the post-marketing safety of venlafaxine using data from the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS).MethodsThe data were extracted from the FAERS database from the first quarter (Q1) 2004 to Q2 2025. Adverse drug events were analyzed using the Reporting Odds Ratio (ROR), Bayesian Confidence Propagation Neural Network (BCPNN), Proportional Reporting Ratio (PRR), and Multi-Item Gamma Poisson Shrinker (MGPS) methods.ResultsA total of 47,325 venlafaxine-related adverse event reports were analyzed. Disproportionality analysis revealed significant signals for drug ineffectiveness (n = 2,108, ROR = 1.6, PRR = 1.6, χ2 = 483.4, IC = 0.7, EBGM = 1.6), drug hypersensitivity (n = 1,014; ROR = 4.9, PRR = 4.8, χ2 = 2998.7, IC = 2.2, EBGM = 4.7), and anxiety (n = 198, ROR = 4.3, PRR = 4.2, χ2 = 2202.0, IC = 2.0, EBGM = 4.1). Strongest signals (EBGM = 9.9) were observed for suicide attempt, agitated depression, and renal dysplasia. Tachycardia (EBGM = 8.3) was the most frequently reported adverse event among patients under 18 years, while emotional disorder (EBGM = 9.5) predominated in those aged 65 years and older. Most adverse events (39.3%) occurred within the first 30 days of venlafaxine therapy initiation.ConclusionThis pharmacovigilance analysis systematically identified significant safety signals associated with venlafaxine. The findings provide important evidence to support safer clinical use of venlafaxine and may assist in optimizing individualized therapeutic decisions in practice.